Interactions among energy consumption, economic development and greenhouse gas emissions in Japan after World War II. (February 2016) - Lu, Hong-fang; Lin, Bin-le; Campbell, Daniel E.; Sagisaka, Masayuki; Ren, Hai
Abstract: The long-term dynamic changes in the triad, energy consumption, economic development, and Greenhouse gas (GHG) emissions, in Japan after World War II were quantified, and the interactions among them were analyzed based on an integrated suite of energy, emergy and economic indices. The results quantitatively showed that two different energy strategy periods, one before 1973 using new sources of higher quality energy and one after 1973 focused on improving the efficiency of energy generation methods, could explain the linear increase in national economic development in Japan over the 66 years from 1946 to 2011. Japan benefited both ecologically and economically from importing fossil fuels, which accounted for 8.7% of the nominal GDP of Japan averaged over the entire study period. The total environmental impacts of GHG (i.e., CO2, CH4 and N2 O) emissions measured by emergy decreased after 1997, and since 2009 they have remained lower than 76% of the emissions in 1990, even though no decrease in the global warming impact based on the weight of CO2 was observed. Emergy methods and Energy Systems models revealed aspects of the complicated interactions among energy consumption, economic development, and the potential environmental impact of GHG emissions which formerly had not been recognized.